Model Pembelajaran Kooperatif Berbasis Asesmen Otentik pada materi Surat Al Alaq di SDIT Permata Mulia - Nurul Faizatus Sholikah; Romelah Romelah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education (PAI) learning is not only aimed at improving students' knowledge, but also forming Islamic attitudes and behaviors according to religious values. This study aims to develop authentic assessments integrated into cooperative learning models in Islamic Religious Education (PAI) subjects in Elementary Schools by focusing on the material of Surah Al Alaq. Authentic assessments are used to assess students' cognitive, affective, and psychomotor aspects more comprehensively in a real-world context. This assessment is designed to improve students' understanding of Surah Al Alaq, which includes the content, values ​​of faith and knowledge, and the spirit of learning as contained in Surah Al Alaq. The research method used is a case study with a qualitative approach. The results of the study indicate that the use of authentic assessments in cooperative learning increases student participation, understanding of Islamic values, and cooperation skills. This study provides recommendations for educators to implement authentic assessment as an integral part of cooperative learning, especially in Al-Quran materials such as Surah Al-Alaq to create more meaningful learning in Islamic Religious Education subjects